L-citrulline and L-arginine improve reproductive performance in primiparous and multiparous cows via distinct shared metabolic pathways and pyrimidine metabolism - Fan, Chen; Chen, Changzheng; Liu, Renping; Maimaiti, Muredili; Li, Changgeng; Zao, Weijie; Lv, Waike; Xu, Guozhu; Zhao, Guodong (Frontiers in Veterinary Science, 2025)
BackgroundTo investigate the impact of L-arginine (L-Arg) and L-citrulline (L-Cit) on cow reproductive performance.Methods90 healthy, age-matched Simmental cows were randomly assigned to three groups: control, L-Arg, and L-Cit, with 30 cows per group. Estrus synchronization was performed, and various parameters were assessed, including estrus rate, conception rate, and early embryo apoptosis, following intraperitoneal administration of L-Arg and L-Cit. Additionally, reproductive hormones, serum antioxidant levels, and plasma metabolites were measured.ResultsResults indicated that both the estrus and conception rates in the L-Arg and L-Cit groups were significantly higher than those in the control group (p < 0.05). Furthermore, serum LH levels and VEGF concentrations on day 1 and day 8 were elevated in the L-Arg and L-Cit groups compared to controls (p < 0.05). Estrus rate and serum NO concentration in the L-Cit group were notably higher than those in the control group (p < 0.05). At day 8 and day 21, estrus rate, conception rate, P levels, and serum VEGF concentrations were significantly greater in both the L-Arg and L-Cit groups compared to controls (p < 0.05). Additionally, serum NO concentration was significantly higher in the L-Cit group than in the control group (p < 0.05). The activities of T-AOC and GSH-Px in serum were significantly increased in both primiparous and multiparous cows in the L-Arg and L-Cit groups relative to the control group (p < 0.05). Metabolomic analysis revealed that in primiparous cows, the protein digestion and absorption, ABC transporters, and AMPK signaling pathways were significantly enriched. In multiparous cows, pyrimidine metabolism was notably enriched.ConclusionUnder the experimental conditions, L-Arg modulated the production of Dimethyl sulfone, 1,5-pentanediamine, Bassanolide, and Phenylalanine in primiparous cows through the protein digestion and absorption and ABC transporters pathways, while L-Cit influenced the same metabolites via the ABC transporters pathway. Both L-Arg and L-Cit promoted increased NO, GSH-Px, T-AOC, and VEGF levels, enhancing early embryo implantation. Additionally, L-Arg and L-Cit synergistically influenced pyrimidine metabolism, regulating the production of N-myristoylphosphorylcholine, N-oleoyl-d-erythro-sphingosylphosphorylcholine, 1-stearoyl-2-docosahexaenoyl-sn-glycero-3-phosphocholine, and 1-docosahexaenoyl- 2-stearoyl-sn-glycero-3-phosphocholine. This modulation resulted in increased NO, GSH-Px, T-AOC, and VEGF in multiparous cows, ultimately supporting early embryo implantation.